Bilayer polymer/fullerene solar cells with a liquid crystal - Canli, N. Yilmaz; Boroglu, M. Safak; Bilgin-Eran, B.; Gunes, S. (ELSEVIER SCIENCE SA, 2014)
In this paper the effect of 5-(10-undecenyloxy)-2-[[[4-hexylphenyl] imino] methyl] phenol liquid crystal addition into poly(3-hexylthiophene): fullerene containing solar cells were investigated. Based on current-voltage characteristics, we report on the efficiency enhancement for bilayer heterojunction solar cells using this liquid crystal. Crown Copyright (C) 2013 Published by Elsevier B.V. All rights reserved.
Keywords: Poly(3-hexylthiophene); Fullerene; Organic photovoltaics; Solar cells; Liquid crystals; Power conversion efficiency; FIELD-EFFECT TRANSISTORS; POSTPRODUCTION TREATMENT; POLYMER; EFFICIENCY; ALIGNMENT; BLENDS; BUCKMINSTERFULLERENE; HEXABENZOCORONENE; HETEROJUNCTIONS; Materials Science; Physics